The use of used materials as hand washing soap dispensers in preventing the spread of Covid-19 in the village of Bambapuang - Dian Firdiani; Aminullah Aminullah; Saidang Saidang; Ismaya Ismaya; Ismail Ismail; Umiyati Jabri; Elihami Elihami; Ita Sarmita Samad (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2021)
The manufacture of hand soap dispensers is aimed at all people in need in the village of Bambapuang, Anggeraja District, Enrekang Regency, to help the community implement healthy living, especially being aware of the importance of washing hands considering the conditions during the covid 19 pandemic. We make innovations in utilizing household waste, such as using used bottles to become hand soap dispensers by attaching pamphlets to socialize the importance of washing hands.